Transferability and Commercialization of Patent Rights: Economic and Practical Perspectives - Haim V. Levy (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The transformation of innovation into commercial value depends primarily on appropriate protection of the intellectual property, usually by patents, and efficient pathway(s) of its transferability as well as the transfer of the protected knowledge. The key features of patents, from an economic perspective, are that they encompass new knowledge and confer monopoly rights to the owner. The exclusiveness of patent rights is generally conceived as a necessary mechanism to ensure further innovation, stimulate advanced research and facilitate efficient market transactions with patent rights. The patent holder can transfer the technology embodied by way of granting to others a license to use the patented invention in return for a share of the revenues, usually royalties. Patent rights transferability has been proven to be efficient and profitable to the industry as well as beneficial to the welfare of society. The economic and practical perspectives of the transferability and commercialization of patent rights are discussed.